Particles of clay-based antimicrobial particles

By using a specific proportion of bipolar antimicrobial particles, binder and coating agent in viscous compositions such as toothpaste, the problem of uneven distribution of bipolar antimicrobial materials is solved, and uniform distribution and Good visual appearance.

CN119421688APending Publication Date: 2025-02-11UNILEVER IP HLDG BV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380043950.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, bipolar antimicrobial materials are unevenly distributed in viscous flowable compositions such as toothpaste, resulting in spatial separation phenomena and visual appearance problems, and traditional rheological additives cannot effectively solve these problems.

Method used

By extrusion, the granule composition comprising 30% to 70% by weight of bipolar antimicrobial particles, 10% to 40% by weight of water-insoluble binder and 5% to 23% by weight of water-insoluble coating agent. The effluent and spheroidization process forms spherical particles to ensure uniform suspension in viscous liquid.

Benefits of technology

The uniform distribution of bipolar antimicrobial materials in personal care compositions is achieved, reducing the possibility of spatial separation phenomena, and improving the visual appearance and use effect of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161106320000141
    Figure BDA0005161106320000141
  • Figure BDA0005161106320000151
    Figure BDA0005161106320000151
  • Figure BDA0005161106320000171
    Figure BDA0005161106320000171
Patent Text Reader

Abstract

The present invention relates to antimicrobial particles in particulate form and cosmetic and home care compositions comprising such particles. The present invention relates to an antimicrobial particle comprising a clay and a quaternary ammonium compound wherein the clay is an asymmetric 1: 1 or 2: 1: 1 type clay having alternating tetrahedral and octahedral flakes which terminate in tetrahedral flakes at one outer surface plane and in octahedral flakes at the other outer surface plane, each of said flakes comprising a coordinating cation, and a quaternary ammonium compound wherein the clay is a clay of asymmetric 1: 1 or 2: 1: 1 type having alternating tetrahedral and octahedral flakes which terminate in tetrahedral flakes at one outer surface plane and in octahedral flakes at the other outer surface plane, each of said flakes comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordination cations on at least one outer surface plane. The particulate composition has 30 to 70% by weight of bipolar antimicrobial particles, 10 to 40% by weight of a water insoluble binder; and to 20% by weight of a water insoluble coating agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to antimicrobial particles in granular form, and to cosmetic and home care compositions comprising such particles. Background Art

[0002] Various cosmetic and home care compositions are known to have a number of end-use benefits through agents including fragrances, antimicrobials and sunscreens. Sometimes benefit agents are encapsulated or granulated to make them, for example, more effective or more stable.

[0003] WO2011036031 A1 (Unilever) discloses a bipolar antimicrobial particle, wherein the precursor is an asymmetric 1:1 or 2:1:1 type clay particle comprising alternating tetrahedral and octahedral sheets terminating with tetrahedral sheets at one external surface plane and terminating with octahedral sheets at another external surface plane, and having an antimicrobial group attached to a coordinating cation on one of the external surface planes, the antimicrobial group being selected from a long chain quaternary ammonium compound comprising a single alkyl or alkenyl group having an average chain length greater than or equal to C20, or selected from cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride (BKC), benzethonium chloride, cetrimide, quaternary ammonium salts, polyhexamethylene BH, antimicrobial alcohols, antimicrobial phenols, antimicrobial organic acids / salts, zinc pyrithione, ketoconazole, The quaternary ammonium compound having antimicrobial properties is fixed on clay serving as a carrier.

[0004] WO 2014 / 102032 A1 (Unilever) discloses a toothpaste comprising the aforementioned bipolar antimicrobial particles.

[0005] US2012121669 A1 (Colgate-Palmolive) discloses an oral care composition comprising a capsule.

[0006] US2008242767 A1 (Colgate) discloses polymer microcapsules for dentifrice. The microcapsules remain intact during the manufacture and storage of toothpaste. The 5 to 50 μm microcapsules are said to have good mechanical properties to withstand shear forces up to about 1000 / s during mixing and high-speed filling; good temperature stability, allowing the capsules to remain intact at temperatures up to about 70°C; good chemical stability, allowing the capsules to be stable in the presence of sodium lauryl sulfate and at pH 5 to 8. The microcapsules rupture and release CPC directly into the oral cavity without forming inactive complexes.

[0007] KR20040081936 A (Dong A Pharm, 2004) discloses a toothpaste containing CPC particles, i.e., 0.01 to 5 wt% CPC based on the total weight of the composition, wherein CPC is coated on the surface of particles made of precipitated calcium carbonate, silicon dioxide, zeolite, colloidal silicon dioxide and anhydrous calcium phosphate. The particle size of the particles is 100 to 750 μm, and the strength is 150 to 650 g / cm -2 .

[0008] WO 2021 / 259748 A1 (Unilever) discloses an oral care composition having 0.1 to 10 wt % of bipolar antimicrobial particles and a zinc compound.

[0009] It has been established that the bipolar antimicrobial materials disclosed in WO2011036031 A1 and WO2014 / 102032 A1 are suitable for use in a variety of home and personal care products, particularly oral care products themselves, but the applicant has observed that when formulated into a viscous flowable composition such as toothpaste, which is typically packaged in a toothpaste tube, the bipolar antimicrobial material is not evenly distributed across the length and width of the packaged composition as might reasonably be expected. There are spatially separated zones or regions that are rich in the material and thus the antimicrobial material itself, and correspondingly there are regions of lower concentration. Furthermore, at least for clear or water-white formulations, the bipolar antimicrobial material in powdered or amorphous form may cause problems with the visual appearance of the composition. This visual appearance can be corrected by the use of a masking agent, but the problem of unequal distribution or spatial separation cannot be solved by any masking agent.

[0010] The standard solution is to use rheological additives to prevent the free movement of the bipolar antimicrobial material, but this is undesirable due to the inevitable effect on the viscosity of such compositions.

[0011] Therefore, there is a risk that the antimicrobial material is not evenly distributed in the bulk of the home or personal care composition. As a result, some users are able to dispense and obtain an effective portion of the composition, while some other users may not obtain the effective portion and may never know why, but believe that the portion is effective because it is a true representation of the bulk of the composition.

[0012] It is an object of the present invention to overcome at least one of the drawbacks, limitations, or disadvantages of the prior art. Summary of the invention

[0013] The present application discloses a granular composition, which comprises:

[0014] a) 30% to 70% by weight of bipolar antimicrobial particles;

[0015] b) 10 to 40 wt % of a water-insoluble binder; and

[0016] c) 5 to 23% by weight of a water-insoluble coating agent,

[0017] The antimicrobial particles comprise clay and a quaternary ammonium compound, wherein the clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral and octahedral sheets, terminating with a tetrahedral sheet at one exterior surface plane and with an octahedral sheet at another exterior surface plane, each of the sheets comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordinating cation on at least one exterior surface plane.

[0018] According to a second aspect, a liquid personal care composition is disclosed, the liquid personal care composition comprising particles of the particle composition of the first aspect.

[0019] When the particulate compositions of the present invention are included in liquid compositions, especially viscous liquid personal care compositions, the particles remain uniformly suspended in the matrix of the composition, thereby reducing the likelihood of spatial segregation of such particles typically observed with such compositions.

[0020] The present inventors have discovered that when the bipolar antimicrobial particles are incorporated into a granular composition together with a specific amount of a water-insoluble binder and a water-insoluble coating agent, the granular composition provides a uniform distribution of the antimicrobial agent in the bulk of the personal care composition. The granular composition has been found to have particles that are spherical in shape and they retain their shape and size in the personal care composition. This ensures that the user gets an effective portion of the personal care composition at each dispensing, which represents the bulk composition. DETAILED DESCRIPTION OF THE INVENTION

[0022] "Length", "width" and "thickness" refer to the length, width and thickness of a particle or microcapsule in an unaggregated state. The term "length" refers to the average size of a particle generally along the longitudinal axis. The term "width" refers to the average size of a particle perpendicular to the length and generally perpendicular to the longitudinal axis. The term "thickness" refers to the average size of a particle perpendicular to the length and width. The length, width and thickness can be measured, for example, by scanning electron microscopy (SEM) averaging the values ​​of at least ten particles.

[0023] "Sphericity" is a measure of how closely the shape of an object resembles that of a mathematically perfect sphere. The sphericity of a particle is the ratio of the surface area of ​​a sphere (of the same volume as a given particle) to the average surface area of ​​the particle.

[0024] Sphericity can be measured as follows.

[0025] The SEM image of the silica particle sample representing the silica particle sample was magnified 20,000 times and imported into the photo imaging software, and the outline of each particle was outlined (two-dimensional). For this analysis, particles that are close to each other but not attached to each other should be considered as independent particles. The outlined particles are then filled with color, and the image is imported into a particle characterization software (e.g., IMAGE-PRO PLUS available from Media Cybernetics, Inc., Bethesda, Md.) that can determine the perimeter and area of ​​the particles.

[0026] As used herein, "specific surface area" refers to the specific surface area determined according to the Brunauer-Emmett-Teller method. The value of the specific surface area is measured by satisfying the requirements specified in ASTM Standard D 3663-78.

[0027] Unless otherwise indicated, "particle size" as used herein refers to the diameter of the particles in a non-aggregated state. For a polydisperse sample of particles with a diameter no greater than 1 μm, the diameter means, for example, the diameter measured using an instrument such as a Zetasizer Nano TM The z-average particle size is measured by dynamic light scattering (see International Standard ISO 13321) using the Z-average particle size (Malvern Instruments Ltd, UK). For polydisperse samples with particles larger than 1 μm in diameter, the diameter means, for example, the particle size measured using a system meeting the requirements specified in ISO 13320 (e.g., Mastersizer TM 2000, available from Malvern Instruments Ltd) is the apparent volume median diameter (D50, also called x50, or sometimes d(0.5)) of particles which can be measured by laser diffraction.

[0028] The term "granular" means that the composition of the present invention is in the form of particles. The term granular also means that the composition is neither amorphous nor powdery.

[0029] The present invention

[0030] The granular composition of the present invention comprises:

[0031] a) 30% to 70% by weight of bipolar antimicrobial particles;

[0032] b) 10 to 40 wt % of a water-insoluble binder; and

[0033] c) 5 to 23% by weight of a water-insoluble coating agent,

[0034] The antimicrobial particles comprise clay and a quaternary ammonium compound, wherein the clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral and octahedral sheets, terminating with a tetrahedral sheet at one exterior surface plane and with an octahedral sheet at another exterior surface plane, each of the sheets comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordinating cation on at least one exterior surface plane.

[0035] Bipolar antimicrobial particles

[0036] The granular composition of the present invention comprises 30% to 70% by weight of the bipolar antimicrobial particles. Preferably, the granular composition comprises 35% to 70% by weight, and more preferably 40% to 70% by weight of the bipolar antimicrobial particles. The aforementioned weight % of each component is relative to the total weight of the granular composition.

[0037] It is preferred that the median particle size (D50) of the bipolar antimicrobial particles is from 0.1 μm to 10 μm, more preferably from 0.4 μm to 1 μm and most preferably from 0.5 μm to 0.8 μm. Smaller particle sizes also provide an effective mechanism for increasing the antimicrobial loading, if so desired. The particle size distribution (D50), also known as the median diameter or median of the particle size distribution, is the particle size value at 50% of the cumulative distribution. For example, if the D50 is 5.8 μm, 50% of the particles in the sample are larger than 5.8 μm and 50% of the particles are smaller than 5.8 μm. D50 is generally used to indicate the size of a population of particles. D50 is a size in microns that divides the distribution into half above the diameter and half below the diameter.

[0038] The bipolar antimicrobial particles contain clay and a quaternary ammonium compound.

[0039] The clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral sheets and octahedral sheets, which terminates with a tetrahedral sheet at one external surface plane and an octahedral sheet at another external surface plane, each of the sheets comprising a coordinating cation. A quaternary ammonium compound is attached to the coordinating cation on at least one external surface plane.

[0040] Preferably, when the clay is an asymmetric 1:1 type clay, it belongs to the kaolinite or serpentine family of minerals. When the clay is kaolinite, it is preferably kaolinite, dickite, halloysite or nacrite. When it is serpentine, it is preferably chrysolite, lizardite or lamesite.

[0041] Alternatively, and preferably, the clay is an asymmetric 2:1:1 type clay. Preferably, when the clay is an asymmetric 2:1 type clay, it belongs to the chlorite family of minerals. Chlorites comprise tetrahedron-octahedron-tetrahedron sheets, like 2:1 type clays, with particularly weakly bound brucite-like layers between the tetrahedral layers. The tetrahedral sheets preferably comprise coordinating tetrahedral cations of silicon. The tetrahedral sheets may also include coordinating tetrahedral cations that are not isomorphously substituted with silicon. Isomorphously substituted coordinating tetrahedral cations include, but are not limited to, cations of aluminum, iron or boron.

[0042] It is preferred that the octahedral sheet has coordinating octahedral cations of aluminum. The octahedral sheet may also contain isomorphously substituted coordinating octahedral cations that are not aluminum. Isomorphously substituted coordinating octahedral cations include cations of magnesium and iron. The antimicrobial agent is attached to the coordinating cations on the outside of one of the outer surface planes. Therefore, the antimicrobial agent is preferably attached to the coordinating cations on the outside of the tetrahedral sheet. Alternatively, and preferably, the antimicrobial molecule is attached to the coordinating cations on the outside of the octahedral sheet. The coordinating cations on the outside of each of the tetrahedral and octahedral surface sheets are attached to the antimicrobial agent, provided that the antimicrobial agent attached to the coordinating cations on the outside of the tetrahedral surface sheet is not the same as the molecule attached to the coordinating cations on the outside of the octahedral surface sheet. The antimicrobial agent is preferably attached to the coordinating cations on the outer surface of the octahedral surface plane, rather than preferably attached to the coordinating cations on the inside of the non-external tetrahedron or octahedral plane or surface sheet.

[0043] It is preferred that in the antimicrobial material the antimicrobial agent is attached to coordinating cations on the outer surfaces of the octahedral surface planes.

[0044] In the granular composition of the present invention, it is preferred that the bipolar antimicrobial particles comprise 0.5 to 5 parts by weight of the quaternary ammonium compound and 90 to 98 parts by weight of the clay on a weight / weight basis.

[0045] Preferably, the quaternary ammonium compound is cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride (BKC), benzethonium chloride, cetrimonium bromide, quaternary ammonium salt, tetrabutylammonium bromide, undecylenamidopropyltrimethylammonium methylsulfate, methylbenzethonium chloride, cetethyldimonium bromide, cetromonium tosylate, cocotrimethylammonium chloride, dodecylbenzyltrimethylammonium chloride, laurylisoquinolinium bromide, laurylpyridinium chloride, dequalinium chloride or domiphene.

[0046] Particularly preferably, the antimicrobial agent is cetylpyridinium chloride (CPC). Without being bound by theory, it is believed that the primary activity is related to the cationic charge of its amine group. Thus, cetylpyridinium chloride is attracted to and binds to negatively charged protein moieties on the cell membrane or cell wall of microorganisms and to surfaces that are also generally negatively charged, such as teeth. The resulting attachment to the microorganism disrupts the cell wall structure, leading to leakage of intracellular fluid, and ultimately killing the associated microorganisms.

[0047] It is particularly preferred that the clay precursor is a 1:1 type clay particle. It is further preferred that the clay precursor is kaolinite. It is particularly preferred that the quaternary ammonium compound is cetylpyridinium chloride. It is further particularly preferred that when the clay precursor is kaolinite, the antimicrobial quaternary ammonium compound is cetylpyridinium chloride.

[0048] Methods for preparing bipolar antimicrobial particles

[0049] Any chemical reaction or reaction series in which the antimicrobial quaternary ammonium compound is selectively attached to the coordinating cations on the outer planes of the tetrahedral or octahedral surface planes of the asymmetric clay can be used to prepare the bipolar antimicrobial particles. In order to obtain true bipolar antimicrobial particles, it is preferred that the reaction is selective for only one of the outer planes. By "selective" is meant that more than 50%, preferably more than 75%, more preferably more than 80%, still more preferably more than 90%, even more preferably more than 95%, or even more than 99% of the total antimicrobial molecules are present on one of the outer planes. Chemical reactions or reaction series in which the same antimicrobial molecule is attached to the coordinating cations of both surface sheets, i.e., the octahedral sheet and the tetrahedral sheet, are therefore not preferred.

[0050] The particle having bipolar character may have two distinct regions on its surface, the two regions having different surface characteristics. It is particularly preferred that the particle has two spatially distinct external surfaces, the two external surfaces having different surface characteristics. It is contemplated that various types of anisotropic characteristics may be imparted to the surface of the particle having bipolar character by selecting specific antimicrobial molecules having specific groups and selectively attaching them to the coordinating cations of the tetrahedral and / or octahedral surface sheets.

[0051] The method comprises the steps of contacting the precursor with an inorganic acid, adding an antimicrobial quaternary ammonium compound to the mixture, adjusting the pH of the solution to above 8, heating the mixture to a temperature of 50 to 150° C. with stirring and maintaining for about 30 minutes to 10 hours, and isolating a solid product comprising a bipolar particulate antimicrobial agent. When a temperature greater than 100° C. is applied, a pressure vessel is preferred.

[0052] It is preferred to first treat the raw clay with a mineral acid, preferably hydrochloric acid. The hydrochloric acid is used at a concentration of 0.01 N to 1 N, preferably about 0.1 N. The clay particles with the acid are then stirred. Stirring is typically performed for 10 to 60 minutes, preferably about 30 minutes.

[0053] After the precursor is treated with the mineral acid for about 30 minutes, the pH of the system is preferably adjusted to above 8 by adding 0.1 (M) NaOH to the solution.

[0054] After treating the clay with hydrochloric acid, it is preferred to add the desired antimicrobial molecule to the dispersion.The antimicrobial molecule is then added at a concentration of 0.001 to 30%, preferably 0.01 to 5%, based on the total weight of the dispersion.

[0055] After adding the antimicrobial molecules and adjusting the pH of the dispersion, the solution is preferably heated for 1 to 10 hours, preferably 4 to 8 hours, more preferably about 6 hours, while stirring at 50° C. to 150° C., preferably 70° C. to 90° C., more preferably 80° C. A solid product comprising the bipolar particulate antimicrobial agent is isolated.

[0056] After the reaction, the dispersion mixture is preferably centrifuged to obtain the bipolar antimicrobial particles as a residue. Then, it is preferably washed with a large amount of water and then with a ketone solvent (e.g., acetone). Thereafter, it is dried in an oven to obtain the final product.

[0057] In this reaction, the antimicrobial quaternary ammonium compound is preferably attached to the coordinating cations of the octahedral sheet by covalent bonding. The antimicrobial particles prepared by this method have different wettability characteristics for the two outer surface planes.

[0058] Size and Sphericity

[0059] Preferably, the particles of the composition are spherical with a sphericity of 0.7 to 1.0. However, a certain degree of non-sphericity will not impair the performance of the particle composition. More preferably, the sphericity is 0.75 to 1.0, and more preferably 0.8 to 1.0. A sphericity of 1.0 means a perfectly spherical particle. Without being bound by theory, it is believed that when the sphericity is 0.7 to 1.0, the particles are more effective than when outside this range. This is especially true when the particles are used in viscous liquid home care and personal care compositions.

[0060] Preferably, the bulk density of the granular composition is from 0.800 to 0.950 g / cm 3 Further preferably, the average particle size of the particles is 650 to 900 μm.

[0061] Preferably, the particles of the granular composition are friable and have a friability of 0.6 to 0.9 w / w. In particularly preferred compositions of the invention, the particles should be insoluble in the medium of the composition into which it is incorporated. In the context of this application, "insoluble" means having sufficient insolubility to keep the particles insoluble or substantially insoluble in the composition at ambient temperature, so that their friability, and therefore their ability to perform their intended function, under the conditions of use of the composition is not adversely affected.

[0062] Binder

[0063] The granular composition of the present invention comprises 10 to 40 wt% of a water-insoluble binder.

[0064] As used herein, "binder" means a material used to bind two or more other materials in a particle together. Preferably, the binder is a carbohydrate. Preferably, the carbohydrate is starch, more preferably corn starch. When the binder is starch, it is preferred that the amount of starch in the composition is in the range of 10 wt % to 20 wt %, still more preferably 10 wt % to 19 wt %, and further more preferably in the range of 10 wt % to 18 wt %. The binder according to the present invention is a carbohydrate that is not cellulose or a cellulose derivative.

[0065] The granular composition comprises 10 to 40 wt% of a binder, more preferably 10 to 30 wt% of a binder. Preferably, the granular composition comprises at least 11 wt%, also preferably at least 12 wt%, also preferably at least 13 wt%, most preferably at least 15 wt% of a binder, but usually not more than 35 wt%, also preferably not more than 30 wt%, still further preferably not more than 28 wt%, still more preferably not more than 27 wt%, most preferably not more than 25 wt%, still more preferably not more than 20 wt% of a binder, based on the weight of the granular composition.

[0066] Preferably, when the granular composition comprises starch as a binder, it is preferred that the composition comprises from 10 wt% to 20 wt% starch.

[0067] Coating agent

[0068] The granular composition of the present invention comprises 5% to 23% by weight of a water-insoluble coating agent. Preferably, the coating agent is a polymer. Preferably, the coating agent is selected from [meth]acrylates, aminoalkyl [meth]acrylates, cellulose, cellulose derivatives or mixtures thereof. The coating agent may also act as a spheronizer. An example of a spheronizer in the composition of the present invention is preferably microcrystalline cellulose. Preferably, the coating agent is based on [meth]acrylate. Preferably, the [meth]acrylate-based coating agent is a latex dispersion of a neutral polymer produced by emulsion polymerization of, for example, ethyl acrylate and methyl methacrylate. Commercially available coating agents include Eudragit NE 30D and Eudragit NM 30D, which are coating systems based on polymethacrylates. The difference between Eudragit NE 30D and Eudragit NM 30D is the content and nature of the emulsifier.

[0069] It is also preferred that the coating agent is cellulose or a cellulose derivative. Preferably, the coating agent is fibrous cellulose. More preferably, the binder is an alkyl cellulose, and even more preferably, the alkyl cellulose is ethyl cellulose. As used herein, ethyl cellulose polymer means a derivative of cellulose in which some of the hydroxyl groups on the repeating glucose units are converted to ether groups. Preferably, the coating agent can be in any form, including but not limited to solid, liquid dispersion, more preferably aqueous dispersion or mixtures thereof.

[0070] Preferably, when the coating agent is cellulose or a cellulose derivative, it is preferred that the amount of cellulose or a cellulose derivative is in an amount ranging from 5 wt% to 11 wt%, still more preferably from 5 wt% to 10.5 wt%. Without wishing to be bound by theory, the inventors believe that when the amount of cellulose or a cellulose derivative in the granular composition is in an amount above 11 wt%, it causes the granular composition to swell in the presence of water, in particular when the granular composition according to the present invention is incorporated into an oral care composition. This swelling over time has a negative impact on the size and shape of the granular composition during storage.

[0071] Preferably, the coating agent has a low glass transition temperature, more preferably, the glass transition temperature is lower than 132°C, more preferably 40°C to 50°C.

[0072] When both the binder and the coating agent are based on [meth]acrylate polymers, it is preferred that they are different.

[0073] According to the first aspect, the granular composition comprises 5 to 23 wt% of coating agent, more preferably 5 to 15 wt% of coating agent. Preferably, the granular composition comprises at least 6 wt%, also preferably at least 8 wt%, also preferably at least 9 wt%, most preferably at least 10 wt% of coating agent, but usually not more than 19 wt%, also preferably not more than 18 wt%, still further preferably not more than 17 wt%, still more preferably not more than 16 wt%, and most preferably not more than 15 wt% of coating agent, based on the weight of the granular composition.

[0074] It is further preferred that the granular composition of the present invention comprises at least one of a granulation aid or a spheroidization aid.

[0075] Method for preparing granular composition:

[0076] According to another aspect of the present invention, a method for preparing the granular composition according to the first aspect is disclosed.

[0077] A method for preparing a granular composition according to the first aspect of the present invention, the method comprising the following steps:

[0078] (i) mixing bipolar antimicrobial particles, a water insoluble binder, and a water insoluble coating agent to form a mixture;

[0079] (ii) extruding the mixture to form an extrudate;

[0080] (iii) spheronizing the extrudate to form a granular composition,

[0081] The granular composition comprises 30 to 70 weight percent of bipolar antimicrobial particles, 10 to 40 weight percent of a water-insoluble binder, and 5 to 23 weight percent of a water-insoluble coating agent.

[0082] According to a second aspect, a method for preparing a granular composition comprises the step of mixing the bipolar antimicrobial particles, a binder and a coating agent to form a homogenous mixture. Preferably, the mixing is carried out in a mixer. Preferably, the mixer can be any mixer known to those skilled in the art for granulation. Preferably, the ingredients are mixed in a mixer to form a wet mass having a desired consistency.

[0083] Then, preferably, the wet mass is extruded through the die slit of the extruder, and the extrudate coming out of the die slit is cut. Preferably, the wet mass is extruded through, for example, a screw extruder. Although the die slit and thus the extrudate can be in any suitable shape, a spaghetti or noodle shape is more preferred. When the extrudate takes the form of spaghetti or noodles, the extruder die aperture is preferably in the range of about 0.1 mm to about 1 mm, more preferably in the range of 0.4 to 0.8 mm. The extrudate is preferably cut using a high-speed tool set after passing through the drawing plate of the extruder.

[0084] Once the extrudate is converted into a plurality of smaller sized pellets, the next step involves spheronizing the extrudate in a spheronizer to give the pellets a spherical shape. Spheronizers typically deform the pellets through a combination of mechanical force and optionally heat. When the pellets being spheronized are heated, preferably the temperature is at least 1 to 5 degrees above the Tg or melting point of the largest amount of thermoforming material in the pellets.

[0085] Preferably after spheronization, the spheronized extrudate is dried and then preferably sieved to provide a granular composition according to the present invention. Preferably, the drying step is carried out at a temperature of 40 to 60° C. Extrusion / spheronization is a process in which the active ingredient and excipients are sequentially blended, wet granulated, extruded and spheronized to form granules.

[0086] Personal care compositions

[0087] The present invention also relates to a liquid personal care composition comprising the granular composition of the present invention. Preferably, the personal care composition is a leave-in skin lotion, skin cream, antiperspirant, deodorant, serum, shampoo, hair conditioner, hair serum, hair spray, dentifrice, hand soap, shower gel, shower gel or soap.

[0088] It is preferred that the liquid personal care composition is a dentifrice. Preferably, the dentifrice is a toothpaste. Further preferably, the toothpaste is a gel. Typically such a toothpaste is transparent.

[0089] It is preferred that when the dentifrice is a toothpaste, the toothpaste comprises at least one of a calcium-based abrasive or a silica-based abrasive, more preferably a silica-based abrasive. Preferably, the abrasive silica is precipitated silica. Suitable precipitated silicas for use as abrasive amorphous silica particles in the present invention are commercially available and include PQ Corporation sold under the trade name AC43, AC77, AC35 and Those sold as AC 33. Mixtures of any materials may also be used. Preferably, the toothpaste composition comprises from 1 to 10% by weight of abrasive silica.

[0090] Alternatively, the toothpaste contains a calcium-based abrasive. A particularly preferred abrasive is fine ground natural chalk (FGNC). It is obtained from limestone or marble. FGNC can also be chemically or physically modified by coating during or after grinding by heat treatment. Typical coating materials include magnesium stearate and magnesium oleate. The morphology of FGNC can also be changed during the grinding process by using different grinding techniques such as ball milling, air classification grinding or spiral jet grinding. FGNC can be used as the only calcium-containing abrasive. However, FGNC can also be used with other calcium-containing abrasives to balance abrasion. Other preferred calcium-containing abrasives include dicalcium phosphate (DCP), calcium pyrophosphate and precipitated calcium carbonate (PCC). When a combination of calcium-containing abrasives is used, it is preferred that FGNC is 35 to 100% of the total abrasive, more preferably 75 to 100% and especially 95 to 100%. In this case, the remainder is most preferably PCC.

[0091] Preferably, the toothpaste comprises 40 to 85 wt % of a liquid continuous phase based on the total weight of the dentifrice. Such a liquid continuous phase generally comprises a mixture of water and a polyol in different relative amounts, the amount of water generally being in the range of 10 to 45 wt % (based on the total weight of the dentifrice) and the amount of the polyol generally being in the range of 30 to 70 wt % (based on the total weight of the dentifrice).

[0092] For a soft and supple mouthfeel, a humectant is typically included in toothpaste. Humectants also reduce the tendency of toothpaste to lose moisture. Preferred toothpaste compositions contain 3.5 to 40% by weight of humectants. Further preferred compositions have 10 to 40% by weight, more particularly 10 to 20% by weight of humectants. A particularly preferred humectant is sorbitol, which is typically obtained as a 70% aqueous solution. Other preferred humectants include glycerol, maltitol, and xylitol. More preferred toothpastes contain glycerol and sorbitol for a lubricated mouthfeel, but their cumulative content should not exceed the disclosed upper limit. Lower humectant content provides an effective way to reduce product costs.

[0093] It is preferred that the toothpaste contains a binder or thickener in an amount of 0.5 to 10% by weight, based on the total weight of the dentifrice. Suitable binders or thickeners include carboxyvinyl polymers (such as polyacrylic acids crosslinked with polyallyl sucrose or polyallyl pentaerythritol), hydroxyethyl cellulose, hydroxypropyl cellulose, water-soluble salts of cellulose ethers (such as sodium carboxymethyl cellulose and sodium carboxymethyl hydroxyethyl cellulose), natural gums (such as carrageenan, karaya gum, guar gum, xanthan gum, gum arabic and tragacanth), finely divided silica, hectorite, colloidal magnesium aluminum silicate and mixtures thereof.

[0094] It is further preferred that the toothpaste of the present invention comprises a surfactant in an amount of 0.2 to 10% by weight based on the total weight of the dentifrice. Suitable surfactants include anionic surfactants such as sodium salts, magnesium salts, ammonium salts or ethanolamine salts of C8 to C18 alkyl sulfates (e.g., sodium lauryl sulfate), C8 to C18 alkyl sulfosuccinates (e.g., sodium dioctyl sulfosuccinate), C8 to C18 alkyl sulfoacetates (e.g., sodium lauryl sulfoacetate), C8-C18 alkyl sarcosinates (e.g., sodium lauryl sarcosinate), C8 to C18 alkyl phosphates (which may optionally contain up to 10 ethylene oxide and / or propylene oxide units) and sulfated monoglycerides. Other suitable surfactants include nonionic surfactants such as optionally polyethoxylated fatty acid sorbitan esters, ethoxylated fatty acids, esters of polyethylene glycol, ethoxylates of fatty acid monoglycerides and diglycerides, and ethylene oxide / propylene oxide block polymers. Other suitable surfactants include amphoteric surfactants such as betaines or sultaines.

[0095] Further preferably, the toothpaste comprises, in addition to the clay present via the bipolar antimicrobial particles, montmorillonite clay. Montmorillonite constitutes one of the classes of natural aluminosilicate minerals known as phyllosilicates or layered silicates. Preferred montmorillonite clays are selected from montmorillonites (bentonites, hectorites and their derivatives); purified magnesium aluminum silicates (various grades available as VEEGUM (R) Commercially available from RT Vanderbilt Company); purified sodium magnesium silicate (various grades available as LAPONITE (R) commercially available); organically modified smectites, including tetraalkyl and / or trialkyl ammonium smectites (organically modified montmorillonite clays), such as quaternium-18 bentonite, quaternium-18 hectorite, stearalkonium bentonite and stearalkonium hectorite / and mixtures thereof. Magnesium aluminum silicate clays are particularly preferred. Examples are VEEGUM (R) HV. Clay tends to swell when exposed to water. Preferred toothpaste compositions contain 0.2 to 3 wt. % clay. More preferred compositions include 0.5 to 1 wt. % clay.

[0096] Montmorillonite clay not only plays a role in the sensory profile as believed, but also plays a role in thickening the composition.

[0097] Further preferably, the toothpaste comprises a zinc salt, preferably zinc sulphate or zinc chloride, more preferably zinc sulphate heptahydrate.Preferably, the level of zinc salt is from 0.05 to 1.0 wt %, more preferably from 0.1 to 0.5 wt % of the total composition.

[0098] The composition of the present invention may contain a preservative, preferably sodium benzoate. Preferably, the level of preservative is from 0.1 wt% to 1 wt% of the total composition. Preferably, the composition has a pH of from 4 to 10, more preferably from 7 to 9 at 20°C.

[0099] The composition of the present invention may also contain a deposition aid. In the context of the present invention, the term "deposition aid" generally means a substance that further aids the deposition of the brightener from the composition. An example is polystyrene sulfonate. Another example is polymer.

[0100] The dentifrice composition may also contain other optional ingredients conventional in the art, such as fluoride ion sources, anticalculus agents, buffering agents, flavoring agents, sweeteners, coloring agents, opacifiers, preservatives, anti-sensitivity agents and antimicrobial agents.

[0101] Preferably, the personal care composition comprises from 0.1 wt% to 3 wt% of the granular composition according to the present invention, even more preferably the personal care composition comprises from 1 wt% to 2.5 wt% of the granular composition.

[0102] Various examples will be presented below that illustrate the invention, which examples should in no way be considered as limiting the scope of the invention.The invention will now be explained with the aid of the following non-limiting examples. DETAILED DESCRIPTION

[0103] Example

[0104] Example 1: Preparation of antimicrobial particles (CPC-clay)

[0105] Five grams of kaolinite were placed in 500 ml of 0.1 N HCl solution and ultrasonicated for 30 minutes. Then, the pH was raised to 9 by dropping a NaOH solution. 10 g of CPC (cetylpyridinium chloride) was added thereto, and the suspension was stirred on a magnetic stirrer for six hours while maintaining the temperature of the solution at 75 to 80 ° C. The suspension was then washed with water about ten times to remove excess CPC and finally washed with ethanol. The clay was then dried in a hot air oven. The composition prepared as above contained 97.5% by weight of kaolinite and 2.5% by weight of cetylpyridinium chloride. The D50 of the particles was 0.5 μm.

[0106] Example 2

[0107] In this experiment, the bipolar antimicrobial particles of Example 1 were granulated according to the process briefly described below.

[0108] Weigh all raw materials according to the requirements of the relevant formula.

[0109] The excipients (if any) are blended and mixed thoroughly in a planetary mixer at low rpm for 2 to 5 minutes. Then, the granulation liquid is added to the dry blend in small amounts and mixed thoroughly. The process steps are repeated until a wet mass of the desired consistency is obtained. Then, the wet mass is extruded at a speed of 50 rpm using a 0.8 mm die. The extrudate is spheronized, ensuring a balance between spheronization speed, time and spheronizer plate size. The resulting pellets are dried at 60°C until all pellets are completely dry. The pellets are sieved to obtain particles within a specified size range.

[0110] Example 3: Comparative Example

[0111] Granules of different compositions were prepared for comparative analysis. The details of the compositions are shown in Table 1. All granule compositions of Table 1 are comparative examples, i.e., not within the scope of the present invention.

[0112] Table 1

[0113]

[0114] Observations:

[0115] A to D: Particles are unstable when included in standard gel toothpaste

[0116] E: Medium hard spherical noodles

[0117] F: Long thin noodles - particles curl during spherification

[0118] G: Powder particles

[0119] H: No particles formed

[0120] I: Forming rod-shaped pellets

[0121] When the particles / sticks / noodles in Table 1 were used to prepare a series of gel toothpaste compositions (A1 to I1), it was observed that the particles / sticks / noodles were unstable and lost their shape and structure during a short storage duration (10-15 days). Therefore, none of the above compositions are suitable for incorporation into gel toothpaste compositions. For details on the basic composition of gel toothpaste, reference may be made to Table 4.

[0122] Example 4

[0123] The purpose of this experiment is also to prepare granules, but all granule compositions in Table 2 are within the scope of the present invention.

[0124] Table 2

[0125]

[0126] In the granule compositions provided in Table 2, CPC-clay is the bipolar antimicrobial particle, corn starch is the water-insoluble binder, and MCC, Eudragit NM 30D, Eudragit RSPO, Ethylcellulose Dispersion Type B NF, Eudragit NE 40D (40 w / w %), Ethylcellulose (Ethocel Standard 45) are used as water-insoluble coating agents.

[0127] In each case, the particles were formed at 1400 rpm for 20 minutes. The particles were observed to be spherical and in particle compositions 1, 3, 4, 7 and 8, the shape was retained even after five days. Compositions 2, 5 and 6 having only a coating agent and no binder were found to provide non-spherical particle compositions.

[0128] The physical properties of compositions 7 and 8 are listed below in Table 3. Granules 7 and 8 were further tested according to Example 3.

[0129] Table 3

[0130] characteristic Composition 7 Composition 8 Bulk density <![CDATA[0.893g / cm 3 ]]> 0.8771g / ml friability 0.70%w / w 0.66%w / w Particle size distribution --- --- 1180μ 0.3% 1180μ 1003μ 8.0% 1003μ 850μ 61.7% 850μ 710μ 22.45% 710μ 600μ 0.70% 600μ 250μ&fine material 6.67% 250μ&fine material Sphericity 0.8 0.8

[0131] Example 5: Gel toothpaste composition

[0132] All the granular compositions of Table 2 were used to prepare standard gel toothpaste formulations numbered 1A to 8A (1A contained granular composition 1 of Table 2, and so on). The detailed formula of the toothpaste is shown in Table 4.

[0133] Table 4

[0134] Element weight% Sorbitol (70%) 58.0 Thickening Silica 8.5 Abrasive Silica (Medium) 9.0 Abrasive Silica (High) 1.6 SLS 2.7 Particles** 2.5 SCMC 9H 0.7 NaOH solution (10%) 0.3 Water and others 100.0

[0135] **Reference Example 2

[0136] Considering that the toothpaste contained 2.5 wt% of the particle composition of Table 2, the wt% of antimicrobial agent (quaternary ammonium compound, CPC) was estimated to be 0.04% (in the toothpaste composition).

[0137] Example 6

[0138] Two selected toothpaste compositions (7A and 8A) of Table 4 were selected for further experiments. In this case, each toothpaste composition 7A and 8A was packaged in a different toothpaste tube, resulting in a total of 100 tubes (200 ml each) of toothpaste according to composition 7A and another 100 tubes (200 ml each) of toothpaste according to 8A.

[0139] From each set of 100 tubes, 5 tubes are randomly selected for testing. Therefore, there are now two sets of tubes, each containing 5 tubes. A toothpaste sample is drawn from each tube as follows:

[0140] - Three samples from the top section

[0141] - Three samples from the middle section

[0142] - Three samples from the bottom section

[0143] Each sample was tested for CPC (cetylpyridinium chloride) content (present in the granules). The expected amount of CPC is 0.04% by weight of the toothpaste composition. The following observations were recorded.

[0144] Table 5

[0145]

[0146] The data in Table 5 show that the observed values ​​of CPC are nearly constant in all three regions of the tube, thereby indicating that there are no significant differences between the middle layer, top & bottom layers (as in the package) of the composition, and the observed values ​​do not deviate too much from the calculated or expected value of 0.04 wt% (in the toothpaste). In other words, there is no spatial separation into high or low concentration regions of particles (and antimicrobial agents).

[0147] This indicates that when the granular compositions with bipolar antimicrobial particles according to the present invention are incorporated into personal care compositions (toothpaste), consumers receive the same amount of antimicrobial benefit per dispense. Additionally, these granular compositions can also be visually perceived in granular form, and the granular compositions further enhance the overall appearance of the toothpaste (personal care composition) while delivering functional benefits.

Claims

1. A granular composition comprising: a) 30-70 wt % bipolar antimicrobial particles; b) 10-40 wt % of a water-insoluble binder; and c) 5-23% by weight of a water-insoluble coating agent; The antimicrobial particles comprise clay and a quaternary ammonium compound, wherein the clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral and octahedral sheets, terminating with a tetrahedral sheet at one exterior surface plane and with an octahedral sheet at another exterior surface plane, each of the sheets comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordinating cation on at least one exterior surface plane.

2. The granular composition of claim 1, wherein the bipolar antimicrobial particle comprises 0.5-5 parts by weight of the quaternary ammonium compound and 90-98 parts by weight of the clay on a weight / weight basis.

3. The granular composition according to claim 1 or 2, wherein when the clay is an asymmetric 1:1 type clay, it belongs to the kaolinite or serpentine group of minerals.

4. The granular composition according to claim 1 or 2, wherein when the clay is an asymmetric 2:1 type clay, it belongs to the chlorite group of minerals.

5. The composition according to any one of claims 1 to 4, wherein the quaternary ammonium compound is cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride (BKC), benzethonium chloride, cetrimonium bromide, quaternary ammonium salt, tetrabutylammonium bromide, undecylenamidopropyltrimethylammonium methylsulfate, methylbenzethonium chloride, cetyldimethylethylammonium bromide, cetrimonium p-toluenesulfonate, cocotrimethylammonium chloride, dodecylbenzyltrimethylammonium chloride, laurylisoquinolinium bromide, laurylpyridinium chloride, dequalinium chloride or domiphene.

6. The composition of any one of claims 1 to 5, wherein the antimicrobial agent is attached to coordinating cations on the outer surfaces of the octahedral surface planes.

7. The composition according to any one of claims 1 to 6, wherein the water-insoluble binder is a carbohydrate, and the carbohydrate is not cellulose or a cellulose derivative.

8. The composition according to any one of claims 1 to 7, wherein the water-insoluble coating agent is a polymer selected from [meth]acrylates, cellulose, or cellulose derivatives, and mixtures thereof.

9. The composition according to any one of claims 1 to 8, wherein particles of the composition are spherical with a sphericity of 0.7-1.

0.

10. The composition according to claim 9, wherein the bulk density of the granular composition is 0.800-0.950 g / cm 3 .

11. The composition according to claim 9 or 10, wherein the particles have an average particle size of 650-900 μm.

12. A composition according to any one of claims 9 to 11, wherein the particles are friable, having a friability of 0.6-0.9 w / w.

13. A personal care composition comprising particles of the granular composition according to any one of claims 1 to 12.

14. The personal care composition according to claim 13, wherein the personal care composition is a leave-in skin lotion, skin cream, antiperspirant, deodorant, serum, shampoo, hair conditioner, hair serum, hair spray, dentifrice, hand soap, body wash, shower gel or soap.

15. The personal care composition of claim 14, wherein the dentifrice is a toothpaste.

Citation Information

Patent Citations

  • Dental composition for antiplaque and antigingivity

    KR1020040081936A

  • Polymeric Encapsulates Having a Quaternary Ammonium Salt and Methods for Producing the Same

    US20080242767A1

  • Oral care composition comprising capsules

    US20120121669A1

  • An antimicrobial particle and a process for preparing the same

    WO2011036031A1

  • Oral care composition having an adduct of clay and antibacterial agent

    WO2014102032A1